Experiences and Coping Strategies of School Going Breastfeeding Adolescents from Katima-Mulilo and Sesheke Secondary Schools in Sesheke district, Western Province of Zambia - Mooto, Mutakatala; Makukula, Marjorie Kabinga; Sianchapa, Brenda (Journal of Maternal and Child Health, 2023)
Background: The re-entry policy was introduced in Zambia in 1997 to allow pregnant girls to continue their education. However, the increase in dropout rates among re-entered adolescents has become a significant concern in schools, so it is necessary to explore and understand the lived experiences of school-going breastfeeding adolescents. The re-entry policy needs to be revised to protect the school-going breastfeeding adolescent (SGBA) from the challenges related to mothering while schooling. The study aimed to explore the experiences and coping strategies of SGBA in Secondary Schools of Western Province in Zambia. Subjects and Method: The study employed a descriptive phenomenology design the research sample comprised sixteen (16) participants. Fourteen (14) girls re-entered after maternity leave. Nine (9) from Sesheke and five from Katima-Mulilo secondary schools, including two (2) guidance teachers, one (1) from each school. A purposive sampling technique without maximum variation was used. Data generation was through in-depth, semi-structured interview guides and which were audio recorded. In addition, the data underwent manual and Microsoft word coding accompanied by Nvivo version 11 and thematic analysis. Results: The findings revealed that breastfeeding school-going breastfeeding adolescents experienced many challenges in pursuing and completing their school. The challenges ranged from combining roles of schooling and mothering, financial challenges, stigma and discrimination, poor academic performance and lack of breastfeeding space within school premises, including minimal and lack of support from peers and school authority.Conclusion: The data shows the numerous challenges faced by breastfeeding adolescents. Therefore, the Ministry of Education, schools, parents and other stakeholders should review and amend the re-entry policy to enable it to respond to girls’ needs to improve their stay in school and performance. Keywords: Coping Strategies, Breastfeeding, Adolescents, Experiences, School-going. Correspondence: Mooto Mutakatala, Department of Midwifery Women and Child Health, Faculty of Midwifery, University of Zambia, Lusaka, School of Nursing Sciences P O BOX 50110. Email: mootomutakatala@gmail.com. Mobile:+26 0977502912.